Photovoice as a technique to understand the perceptions of local people neighboring Tarangire National Park in Tanzania on the risks caused by migratory animals - Sumay, Gloria, author; Boone, Randall, advisor; Bowser, Gillian, advisor; Wittemyer, George, committee member; Bruyere, Brett, committee member (Colorado State University. Libraries, 2013)
What is the impact of wildlife on communities neighboring national parks and protected areas? Understanding perceptions of risk by local communities on wildlife can help conservation efforts and the development of acceptable policies for parks and protected areas. This study examines communities along the eastern boundary of Tarangire National Park using a combination of Photovoice techniques and individual interviews to determine how these communities perceive risk from wildlife to their agriculture, livestock and economies. Here Photovoice was used to articulate participants' perception of risks to their livelihoods from migratory wildlife that transversed the national park. Three villages (Terrat, Narakauwo and Emboreet) were chosen based on their proximity to wildlife migration corridors and 12 participants from each village were asked to document their perceptions of risk from wildlife using digital cameras. Photovoice uses images taken by participants on a pre-determined topic, followed by interviews of the participants on the photographs to determine themes. In addition, twenty participants from the same villages were interviewed on their perception of risk from wildlife damage using survey questions and narratives. The characteristics of each village (size, distance from each other and distance from park boundary) were determined using GIS and satellite imaginary. The villages had different perceptions (p = 0.003) based on the three categories of risk: wildlife damage, crop damage and shared resources. Village size had no influence on the peoples' perceptions of risk; however land use patterns (farm land and associated activities) showed some influence on perceptions of risk. Changes in land use for two of the villages, Emboreet and Narakauwo, indicated a large increase in farming activities, which are likely to influence peoples' perception of risk. In Emboreet village, which has more farm land, the greatest risk was perceived as crop damage. The results of this study demonstrate the complex relationships between protected areas, migratory wildlife and community villages. To balance the needs to protect highly migratory species such as the wildebeest, conservation managers need to incorporate the perceived risks among villages and the factors that influence those perceptions.
Keywords: perception of risk; Tarangire National Park; photovoice; land covers changes; farm land